Evolving drug regulatory landscape in China: A clinical pharmacology perspective. Issue 4 (23rd February 2021) - Tang, Weifeng; Huang, Ying; Zhou, Diansong; Huang, Yao; Chen, Yingxue; Ren, Song; Li, Yan; Wu, Shengqian; Zhao, Xiaoying; Song, Xuyang; Wang, Haidong; Jin, Yuwen; et al.
Abstract: In order to encourage innovative medicine to address Chinese unmet medical needs, China has changed its drug regulatory landscape to speed up access to new medicines. In order to understand the fast‐changing landscape and to enable planning of more global drug development programs and study designs in China, we reviewed 15 published clinical pharmacology‐related guidances by the National Medical Products Administration (NMPA), and compared them with reference guidances from the US Food and Drug Administration (FDA), the European Medicines Agency (EMA), or the International Conference on Harmonization (ICH), to understand the similarities and differences, especially any China‐specific requirements, such as ethnic sensitivity analysis. Overall, by reviewing these clinical pharmacology‐related NMPA guidances, it is clear that NMPA guidances are very similar to FDA, EMA, and ICH guidances. There are no relevant differences in the major principles, but some differences in structure, contents, and focus were noted. The NMPA is adapting flexibility statements into newly published guidances. Ethnic sensitivity analysis needs to be implemented early in drug development plans. The NMPA encourages sponsors to conduct early clinical trials in China or include China early in multiregional clinical trials, and to obtain safety, efficacy, and pharmacokinetic data for ethnic sensitivity analysis. Depending on the stage of development, ethnic sensitivity analysis can be conducted using in vitro or literature data, other Asian clinical data, or Chinese clinical data.